1979
DOI: 10.1038/icb.1979.36
|View full text |Cite
|
Sign up to set email alerts
|

Antibody Responses to Influenza Vaccines Containing a/Ussr/90/77

Abstract: Summary. Studies were undertaken in adult groups aged 17-24 years, 25-64 years and 66-100 years to determine the haemagglutination-inhibiting antibody responses to sub-unit influenza vaccines containing A/USSR/90/77 (HlNl). Antibody responses to A/USSR/90/77 were low in all groups. The young adult group (17-24 years) produced a primary response to A/USSR/90/77 and showed a significant response to a second dose of vaccine, whereas their responses to the A/Texas/1/77 (H3N2) and B/Hong Kong/8/73 components were o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
4
1

Year Published

1981
1981
1993
1993

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 10 publications
2
4
1
Order By: Relevance
“…The conclusions from this study are that individuals unprimed for A/USSR/77 virus should be immunized twice to afford a protective level of antibody. This is in agreement with findings in other studies (Feery et al 1979;Nicholson et al 1979;Potter et al 1980). After two doses of A/USSR/77 vaccine, subjects primed for the related A/NJ/76 virus possess a lower degree of protection against A/USSR/77 virus than those unprimed for A/NJ/76 virus.…”
Section: Resultssupporting
confidence: 94%
“…The conclusions from this study are that individuals unprimed for A/USSR/77 virus should be immunized twice to afford a protective level of antibody. This is in agreement with findings in other studies (Feery et al 1979;Nicholson et al 1979;Potter et al 1980). After two doses of A/USSR/77 vaccine, subjects primed for the related A/NJ/76 virus possess a lower degree of protection against A/USSR/77 virus than those unprimed for A/NJ/76 virus.…”
Section: Resultssupporting
confidence: 94%
“…This is also illustrated by a second finding, namely that in volunteers with pre-immunization titres < 18 booster immunization did not evoke an increase in the number of participants with protective HI titres. Contrary to this are earlier findings of Feery et al (1979), Potter et al (1980), Kark et al (1981) and Masurel, Ophof& De Jong (1981), who indicated that a second dose of vaccine virus A-HiN1 was necessary to give a more satisfactory level of serum antibody. This discrepancy could perhaps be caused by the fact that participants in the present study under 30 years of age, with pre-immunization titres < 18, for the greater part had undergone infections with viruses related to A/Brazil/11/78 (HINt) virus since 1977, so that the vaccine virus did not encounter virgin soil.…”
Section: Discussioncontrasting
confidence: 66%
“…In contrast to whole virus vaccines, in non-primed subjects split product and subunit vaccines had to be administered in two doses four weeks apart instead of a single dose, to give satisfactory levels of HI antibody. This was established for the A/New Jersey/76 (HINI) vaccine by (among others) the Pandemic Working Group (1977) and Parkman et al (1976), and for the A/USSR/77 (HINt) vaccine by Feery et al (1979) and Potter et al (1980). In the present study an immunization trial was conducted with three different influenza vaccines in volunteers aged 14-30 years and 31-60 years to compare the serological response, clinical reactions, and efficacy in preventing serologically detectable infections.…”
Section: Introductionmentioning
confidence: 99%
“…Although post-vaccination HI antibody levels differed according to the presence or absence of a previous history of natural infection with HlN1 virus, the ratios of significant antibody rises were fairly high and the HI antibody titres would be expected to be protective (Feery, 1979). However, in terms of cross-reactivity of the HI antibody acquired after repeated immunizations to the various antigenic drift strains, a difference was found between persons who had been naturally infected and persons who had only been exposed to HINI virus in the form of vaccine.…”
Section: Serodiagnosis Of Natural Infection With Influenza a Virus Dumentioning
confidence: 98%